Resistance of cocoa to Moniliophthora perniciosa – progenitors and progenies selection - Pires, José Luis; Pires Melo, Gilson Roberto; Macoto Yamada, Milton; Dora Martins, Edna; Luz, Newman (Revista Ceres, 2022)
Witches’ broom, caused by Moniliophthora perniciosa, is the most important cacao disease in Brazil, and the final objective of this study is increasing the level and durability of resistance to this fungus, through the association of different alleles or genes favorable to the character, for the generation of new cocoa varieties. It was conducted, for 10 years, the evaluation of the number of vegetative brooms and cushions brooms per plant, of progenies from a cross breeding scheme in North Carolina II design, with the clones: Be 4, Cepec 89, CSul 7, EEG 29, ICS 98, Oc 67, RB 39 and Scavina 6, as group 1 of progenitors, and CCN 10, CCN 51, Cepec 86, ICS 9, IMC 76, Na 33, P4b, and SGu 54, as group 2. For both groups there were differences in terms of the general combining ability and specific combining ability. Differences among progenitors and among progenies were also found for the tendencies in the evolution of the number of brooms over the evaluation period. And it was possible to increase the level and durability of resistance through the association of alleles or genes favorable to this character, all the three results confirming the original hypothesis.